علاقة النموذج التربوي التعليمي للسيرة النبوية بالضغط النفسي - سلين, صليحة (جامعة الوادي University of Eloued, 2018)
هدفت الدراسة الحالية إلى الكشف عن العلاقة بين النموذج التربوي التعليمي للسيرة النبوية والضغط النفسي لدى أساتذة التعليم المتوسط. وقد جرت الدراسة بمتوسطات الجزائر وسط للسنة الدراسية 2017/2018 حيث تكونت العينة من (160) أستاذ وأستاذة . استخدمت الدراسة استبيان النموذج التربوي التعليمي للسيرة النبوية، ومقياس الضغط النفسي للأساتذة، حيث توصلت الدراسة إلى:عدم استخدام أساتذة التعليم المتوسط للنموذج التربوي التعليمي للسيرة النبوية، وإلى أن أساتذة التعليم المتوسط يعانون من ضغط نفسي مرتفع. كما توصلت الدراسة أيضا إلى وجود علاقة عكسية قوية ذات دلالة إحصائية بين النموذج التربوي التعليمي للسيرة النبوية والضغط النفسي. The study aimed to uncover the relationship between the educational model of the Prophet's biography and the psychological pressure among the teachers of intermediate education. The study was conducted at the averages of Algeria in the academic year 2017/2018, where the sample consisted of(160) teachers. The study used the questionnaire of the educational model of the Prophet's biography and the psychological pressure scale for the teachers. The study found that the teachers of the intermediate education did not use the educational model of the Prophet's biography, and that the teachers of intermediate education suffer from high psychological pressure. The study also found a strong inverse relationship of statistical significance between the educational model of the Prophet's biography and psychological pressure.
لدى أساتذة التعليم المتوسط متوسطات الجزائر وسط نموذجا
مقال
Keywords: النموذج التربوي التعليمي - السيرة النبوية - الضغط النفسي - أساتذة التعليم المتوسط; Educational Model; Biography of the Prophet; Stress; teachers of intermediate education